IMPLEMENTASI KONSEP ITTIHAD ABU YAZID AL-BUSTAMI UNTUK MEWUJUDKAN KELANGGENGAN PERNIKAHAN DALAM RUMAH TANGGA - Subekti, Fiqi Restu; Noni Kensiwi (Program Studi Ilmu Tasawuf IAI Pangeran Diponegoro Nganjuk, Jawa Timur, 2025)
This research is motivated by the phenomenon of the increasing divorce rate each year. Therefore, the researcher offers an alternative solution by examining Abu Yazid al-Bustami's concept of ittihad to achieve marital longevity in family life. One of the objectives of marriage in Islam is to create a family characterized by sakinnah (tranquility), mawaddah (love), and rahmah (compassion). Thus, Abu Yazid al-Bustami's concept of ittihad is highly relevant for implementation in marital relationships. By doing so, the ultimate purpose of marriage as envisioned in Islam can be realized. This study employs a qualitative method with a literature review approach. The research procedure begins by collecting various literary sources on Abu Yazid al-Bustami's concept of ittihad, which are then analyzed by contextualizing and implementing them to achieve marital longevity in family life. The results of this study reveal that Abu Yazid al-Bustami's concept of ittihad consists of three phases: fana, baqa, and the culmination, ittihad. The implementation of fana involves eliminating ego in both partners. The implementation of baqa is reflected in ongoing togetherness based on mutual loyalty and commitment. Finally, the implementation of ittihad itself signifies unity, a deep spiritual bond between the partners that becomes inseparable. Consequently, marital longevity in family life can be achieved.